The effect of flow partition on storm runoff and pollutant retention through raingardens with and without subsurface drainage. (15th January 2022) - Xu, Qing; Jia, Zhonghua; Tang, Shuangcheng; Luo, Wan
Abstract: Green infrastructures (GIs) have been advocated worldwide to mitigate the negative impact of urbanization on regional hydrological cycle, their functions are closely related to their design features and the local environmental condition. This paper reports a field monitoring study that aimed to investigate how runoff partition in raingardens would affect flow and pollutant retention. A paired field experiment was conducted to compare runoff and pollutant retentions in two raingardens with and without subsurface drainage in a shallow water table area. Concentrations of ammonia nitrogen (NH3 –N), nitrate nitrogen (NO3 –N) and total phosphorus (TP) were measured at raingarden inflow, overflow and drainage paths. The results from 28 monitored storm events over two years showed that the raingarden without subsurface drainage achieved its retention mainly through ponding and infiltration, its pollutant retention rates (76% for TP, 81% for NO3 –N, and 79% for NH3 –N) were higher than its runoff retention rate (61%), indicating a first flush effect on pollutants retention in the raingarden during storm events, especially when the raingarden was empty and dry. The raingarden with subsurface drainage facilitated quick discharge of water, the observed runoff reduction through the raingarden was 36%; pollutant removal rates were quite variable: NH3 –N was removed by 91% while the NO3 –N and TP were increased by 3–47%. These results suggest that facilitating specific processes for targeted pollutants is necessary for achieving substantial pollutant removal in a stormwater retention device. Subsurface drainage pipes resulted in short circulating of runoff and lowered pollutant removal rates in the raingarden. Considering the water table fluctuation during the experimental period, we recommend to build infiltration-based GI devices to better capture first flush in intensively developed urban area, which caused deeper groundwater table. In conclusion, installations of different GI devices in urban landscape need to consider the local environmental conditions and facilitate the design features to meet specific storm runoff and pollutants mitigation requirement. Graphical abstract: Image 1 Highlights: Compared flow and pollutants retention in two raingardens with and without subsurface drainage pipe. Subsurface drainage eliminated most overflows from the raingarden but the short retention time lowered pollutant removal rate. Low initial concentration, flushing and short contacting time led to negative effect on TP, complete removal of NH3 –N and no net change of NO3 –N in subsurface drainage. Preferential flow may be the cause for fast drainage, offsetting the positive effect of pollutant adsorption by soil particles. Infiltration-based GI devices could better capture first flush in intensively developed urban area with deeper groundwater table.